ANALISIS DAMPAK PENERAPAN PSAK 72 TERHADAP KINERJA KEUANGANPERUSAHAAN: STUDI KASUS PADA DUA PERUSAHAAN PROPERTI DI INDONESIA - Mutiha, Arthaingan H. (UI Scholars Hub, 2023)
This study aims to analyze the impact of the implementation of PSAK 72 on the financial performance of two properties companies in Indonesia, namely PT Pakuwon Jati Tbk and PT Ciputra Development, Tbk using financial ratios, such as Liquidity Ratios, Profitability Ratios, Solvabilitas Ratios. The research method in this study is a mixed method with a sequential explanatory approach. Quantitative research was carried out with quantitative descriptive to provide an overview of the company's financial performance before and after the implementation of PSAK 72 using a paired sample t test, then qualitative research was carried out using content analysis through the Notes of the Financial Statements and the Company's Annual Report. The results of this study are the Liquidity Ratio of two companies decreased in 2020, the Profitability Ratio of PT Pakuwon Jati decreased while PT Ciputra Development was relatively stable. Solvabilitas ratio of the two companies is relatively stable. While in paired sample t test, there were differences in the Liquidity Ratio and Profitability Ratio of PT Pakuwon Jati before and after the implementation of PSAK 72, there was no difference in Solvency Ratio before and after impelementation of PSAK 72. On the other hand, there was no difference in all the ratios of PT Ciputra Development Tbk before and after the implementation of PSAK 72.